Markers of neuroinflammation influence measures of cortical thickness in bipolar depression. (30th March 2019) - Poletti, Sara; Leone, Giovanni; Hoogenboezem, Thomas A.; Ghiglino, Davide; Vai, Benedetta; de Wit, Harm; Wijkhuijs, Annemarie J.M.; Locatelli, Clara; Colombo, Cristina; Drexhage, Hemmo A.; Benedetti, Francesco
Highlights: Serum levels of ICAM-1, CCL4, sDC25 correlated with lower cortical thickness . Serum levels of TNF-α, IL-8, and CCL2 correlated with a higher cortical thickness . Serum levels of TNF-α and IL-8 correlated with lower BOLD responses to moral stimuli. Abstract: We tested if peripheral levels of cytokines and chemokines associate to grey matter volumes, cortical thickness and fMRI neural responses to a moral valence decision task in bipolar patients. ICAM1 and CCL4 negatively correlated with cortical thickness in Inferior Temporal Gyrus, and sCD25 in Parahippocampal Gyrus. TNF-α, Interleukine-8, and CCL2 correlated positively with cortical thickness in the Anterior Cingulate Cortex, and with lower BOLD responses to negative stimuli. Markers of immune activation are associated with measures of brain structural and functional integrity in bipolar depression.